Enhanced bioremediation of triclocarban-contaminated soil by Rhodococcus rhodochrous BX2 and Pseudomonas sp. LY-1 immobilized on biochar and microbial community response - Miao, Lei; Chen, Siyuan; Yang, Hua; Hong, Yaqi; Sun, Liwen; Yang, Jie; Sun, Guanjun; Liu, Yi; Li, Chunyan; Zang, Hailian; Cheng, Yi (Frontiers in Microbiology, 2023)
Triclocarban (TCC), an emerging organic contaminant (EOC), has become a severe threat to soil microbial communities and ecological security. Here, the TCC-degrading strain Rhodococcus rhodochrous BX2 and DCA-degrading strain Pseudomonas sp. LY-1 (together referred to as TC1) were immobilized on biochar to remove TCC and its intermediates in TCC-contaminated soil. Immobilized TC1 significantly increased the removal efficiency of TCC from 84.7% to 92.7% compared to CK (no TC1 cells on biochar) in 10 mg/L TCC liquid medium. The utilization of immobilized TC1 also significantly accelerated the removal of TCC from contaminated soil. Microbial community analysis revealed the crucial microorganisms and their functional enzymes participating in TCC degradation in soil. Moreover, the internal labor division patterns and connections of TCC-degrading microbes, with a focus on strains BX2 and LY-1, were unraveled. This work provides a promising strategy to facilitate the bioremediation of TCC in soil, which has potential application value for sustainable biobased economies.